Plasmodium falciparum drug resistance in Angola - Fançony, Cláudia (2016)
Facing chloroquine drug resistance, Angola promptly adopted artemisinin-based combination therapy as the first-line to treat malaria. Currently, the country aims to consolidate malaria control, while preparing for the elimination of the disease, along with others African countries in the region. However, the remarkable capacity of Plasmodium to develop drug resistance represents an alarming threat for those achievements. Herein, the available, but relatively scarce and dispersed, information on malaria drug resistance in Angola, is reviewed and discussed. The review aims to inform but also to encourage future research studies that monitor and update the information on anti-malarial drug efficacy and prevalence of molecular markers of drug resistance, key fields in the context and objectives of elimination.